Comparative analysis of otolith shape and spatial distribution and size composition of greenland turbot Reinhardtius hippoglossoides matsuurae in the western Bering Sea - Olga A. Maznikova; Pavel K. Afanasyev; Alexey M. Orlov; Roman N. Novikov; Pavel O. Emelin (Известия ТИНРО, 2017)
Comparative analysis of the greenland turbot otoliths (sagitta) is realized on the materials collected in the western Bering Sea within the Russian EEZ (2005-2015) and in the eastern Bering Sea within the United States EEZ (2013-2014). Software package «Shape V.1.3» is used. The otolith shape and some other biological parameters of turbot are considered. Typical forms of the otoliths are described. The otoliths of turbot from the Anadyr Bay are significantly different (p < 0.001) from those from other areas following to MANOVA and PERMANOVA tests. On the contrary, the otoliths from the Olutorsko-Navarinsky and Navarinsky fishery districts are very similar. Beyond unique oceanographic conditions of the Anadyr Bay, the difference could be caused by partial mixing of the turbots in this area with the fish of American origin. However, following to scientific literature, the turbots in the Olutorsko-Navarinsky and Navarinsky districts are also mixed with the fish of American origin, so additional investigations are necessary to understand the reasons of the otolith shape differentiation. A hypothesis on intraspecific organization of greenland turbot in the Bering Sea is proposed.